2003
DOI: 10.1074/jbc.m306516200
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific Binding of prePhoD to Soluble TatAd Indicates Protein-mediated Targeting of the Tat Export in Bacillus subtilis

Abstract: The Tat (twin-arginine protein translocation) system initially discovered in the thylakoid membrane of chloroplasts has been described recently for a variety of eubacterial organisms. Although in Escherichia coli four Tat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…In B. subtilis, cytoplasmic TatA homologs copurify with Tat substrate, suggesting they may be involved in membrane targeting of the precursor (22). Although we have not yet addressed TatA homolog interaction with substrate in Haloferax volcanii, our initial characterization of TatAo and TatAt revealed they stably interact with each other in the cytoplasm.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In B. subtilis, cytoplasmic TatA homologs copurify with Tat substrate, suggesting they may be involved in membrane targeting of the precursor (22). Although we have not yet addressed TatA homolog interaction with substrate in Haloferax volcanii, our initial characterization of TatAo and TatAt revealed they stably interact with each other in the cytoplasm.…”
Section: Discussionmentioning
confidence: 88%
“…It was therefore unexpected that TatA homologs were detected in Haloferax volcanii cytoplasmic fractions as well as in cytoplasmic fractions from B. subtilis and Streptomyces lividans (10,22). The presumed role of TatA from work with E. coli has been formation of the translocation channel for the Tat pathway (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because of the co-fractionation of TatA with membranes, which depended on the hydrophobic N-terminal region of the protein, it has been assumed that TatA must be an exclusively membrane-bound component of the Tat system (35). However, electron microscopy of TatA d from Bacillus subtilis revealed that a significant portion of this TatA was present in the cytoplasm where it was able to bind the Tat substrate PhoD (8,26). The TatA d , which interacted with membranes, had substrate bound to it (9).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it has been proposed that DmsD performs a "masking" function by binding to the DmsA signal sequence and rendering it unavailable to direct protein export until after DmsA cofactor attachment has been completed (72). In separate studies, Pop et al present tantalizing evidence that Bacillus subtilis TatA interacts with the Tat-dependent prePhoD substrate prior to its own membrane integration (60), implying that cytoplasmic TatA might chaperone Tat preproteins directly to the site of translocation. Given the involvement of molecular chaperones, a vital question is when do they become associated with preproteins?…”
Section: Vol 186 2004mentioning
confidence: 99%